A NEW TYPE OF TRAP FOR CAPTURING ORYCTES RHINOCEROS (SCARABAEIDAE, DYNASTINAE), THE MAIN PEST IN YOUNG OIL PALM AND COCONUT PLANTINGS - Morin J.-P.; Ps. Sudharto; R. Purba; R Desmier de Chenon; T. Kakul; S Laup; L. Beaudoin-Ollivier; D. Rochat (International Coconut Community, 2001)
Oryctes rhinoceros (Scarabaeidae, Dynastinae) trapping is possible with the pheromone (ethyl 4-methyloctanoate) as the attractant. This article describes a new type of trap that functions without insecticides or water, and can remain in place for several months without any particular maintenance so long as the attractant does not run out. As it is 2 m tall, it offers the advantage of having the silhouette of a palm stem, which is visually attractive to this insect